Citra dan Peran Perempuan dalam Cerita Rakyat Ni Anteh Pergi Ke Bulan dengan The Bamboo-Cutter’s Tale - Poppy Mega Karina; Yulianeta Yulianeta; Halimah Halimah (Universitas Pendidikan Indonesia, 2022)
Folklore is a reflection of a society from which we can see how the society lives with various aspects of life including women’s images and roles. This study aims to describe (1) the comparison of structure of the two stories; (2) the comparison of the women’s images in the two stories; and (3) the comparison of the women's roles in the two stories. This study used a comparative qualitative descriptive method with comparative literature studies. Comparative literature studies were based on the comparison of the two stories to identify the similarities and differences with the support of the structuralism theory by A. J. Greimas. Besides, to examine the women’s images and roles, this study used feminist literary criticism. The data were folklore that has been documented in a book entitled Ni Anteh Pergi ke Bulan transcribed by Sukardi (2006) and The Bamboo-Cutter’s Tale transcribed by Kawauchi (2000) which was translated by McCarthy. The data were analyzed by describing the data, interpreting the data, and drawing conclusions. The results of this study indicated that the two stories: (1) have differences in terms of the structure of the story; (2) have similarities and differences in women's self-image and social image; and (3) have similarities and differences in the women’s roles. Based on the women’s images and roles presented in the stories, there is a feminist struggle that discourses on gender equality.